Prognostic Value of Late Gadolinium Enhancement in Postoperative Morbidity following Mitral Valve Surgery in Rheumatic Mitral Stenosis - Putra, Teuku Muhammad Haykal; Sukmawan, Renan; Elen, Elen; Atmadikoesoemah, Celly A.; Desandri, Dwita Rian; Kasim, Manoefris (International Journal of Angiology, 2019)
Myocardial fibrosis in rheumatic mitral stenosis (MS) is caused by chronic inflammatory process. Its occurrence may lead to hemodynamic problems, especially after cardiac surgery. Myocardial fibrosis predicts worse morbidity after cardiac surgery, notably in coronary heart disease and aortic valve abnormalities. However, this issue has not been explored yet among patients with rheumatic MS.The aim of the study was to investigate prognostic impact of myocardial fibrosis to postoperative morbidity after mitral valve surgery in patients with rheumatic MS.This is a prospectively enrolled observational study of 47 consecutive rheumatic MS patients. All patients had preoperative evaluation with cardiac magnetic resonance imaging (CMR) including late gadolinium enhancement (LGE) protocol for left ventricular myocardial fibrosis assessment prior to mitral valve surgery. All patients were followed during hospitalization period. Postoperative morbidities were defined as stroke, renal failure, and prolonged mechanical ventilation.This study involved 33 women (70.2%) and 14 men (29.8%) with a mean age of 46 ± 10 years. Preoperative myocardial fibrosis was identified in 43 patients (91.5%). Estimated fibrosis volume ranged from 0% to 12.8% (median 2.8%). Postoperative morbidities occurred in 11 patients (23.4%). Significant mean difference of myocardial fibrosis volume was observed between patients with and without morbidity after mitral valve surgery (5.97 ± 4.16% and 3.12 ± 2.62%, p = 0.04). This significant association was allegedly influenced by different postoperative hemodynamic changes between the two groups.More extensive myocardial fibrosis is associated with postoperative morbiditiy after mitral valve surgery in patients with rheumatic MS.
Keywords: myocardial fibrosis; rheumatic heart disease; mitral valve surgery